2015
DOI: 10.1016/j.neuropharm.2015.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological stress is required for the anti-alcohol effect of the α3β4* nAChR partial agonist AT-1001

Abstract: Alcohol and nicotine are often taken together. The mechanisms underlying this frequent co-abuse are not well known. Genetic and pharmacological evidence suggests that the nicotinic acetylcholine receptors (nAChRs) containing the α3 and β4 subunits play a role in alcohol as well as nicotine addiction. AT-1001 is a high affinity α3β4 nAChR partial agonist recently found to block nicotine self-administration and relapse-like behavior in rats. Here, to study the involvement of α3β4 nAChRs in the mechanisms that re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 64 publications
(86 reference statements)
2
28
0
Order By: Relevance
“…Testing sessions were conducted every 3–4 days. The day after the experiment, rats were allowed 1 day off and then a new baseline was established over the following 1 or 2 days (Cippitelli et al, 2015b). Data are expressed as mean ± S.E.M.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Testing sessions were conducted every 3–4 days. The day after the experiment, rats were allowed 1 day off and then a new baseline was established over the following 1 or 2 days (Cippitelli et al, 2015b). Data are expressed as mean ± S.E.M.…”
Section: Methodsmentioning
confidence: 99%
“…These well-documented anti-alcohol properties of varenicline seem to be dependent on the activation of α4 nAChRs (Hendrickson et al, 2010). In contrast, α7 (Kuzmin et al, 2009) and α3β4 nAChRs (Carnicella et al, 2010; Cippitelli et al, 2015b) may not be involved in alcohol reinforcement. Consistent with this literature, we have recently demonstrated the efficacy of varenicline in decreasing alcohol self-administration at doses that also decreased nicotine self-administraton in an operant co-administration paradigm (Cippitelli et al, 2015c).…”
Section: Introductionmentioning
confidence: 93%
“…Despite evidence that varenicline decreases alcohol intake (100,108,129), the effects on co-self-administration of nicotine and alcohol are not as clear (130,131). However, withdrawal from chronic concurrent exposure, which is more prolonged than withdrawal from either drug alone, can be attenuated by continued treatment with just one of the drugs (132).…”
Section: Concurrent Use Of Nicotine and Alcoholmentioning
confidence: 99%
“…Therefore, the present series of experiments were designed to investigate the efficacy of AT-1001 in stress-induced reinstatement of nicotine seeking behavior. We have previously shown that AT-1001 had anxiolytic activity in the elevated plus maze assay (EPM) in rats in the presence of a pharmacological stressor yohimbine [41]. Since AT-1001 decreased yohimbine’s anxiogenic effects in the elevated plus maze assay [41], we hypothesized that AT-1001 administration would block yohimbine stress-induced reinstatement of nicotine seeking.…”
Section: Introductionmentioning
confidence: 99%